Probing Nonadiabaticity in the Proton-Coupled Electron Transfer Reaction Catalyzed by Soybean Lipoxygenase - Soudackov, Alexander V. (American Chemical Society, 2014)
[Image: see text] Proton-coupled electron transfer (PCET) plays a vital role in many biological and chemical processes. PCET rate constant expressions are available for various well-defined regimes, and determining which expression is appropriate for a given system is essential for reliable modeling. Quantitative diagnostics have been devised to characterize the vibronic nonadiabaticity between the electron–proton quantum subsystem and the classical nuclei, as well as the electron–proton nonadiabaticity between the electrons and proton(s) within the quantum subsystem. Herein these diagnostics are applied to a model of the active site of the enzyme soybean lipoxygenase, which catalyzes a PCET reaction that exhibits unusually high deuterium kinetic isotope effects at room temperature. Both semiclassical and electronic charge density diagnostics illustrate vibronic and electron–proton nonadiabaticity for this PCET reaction, supporting the use of the Golden rule nonadiabatic rate constant expression with a specific form of the vibronic coupling. This type of characterization will be useful for theoretical modeling of a broad range of PCET processes.